Engineering secure systems: Models, patterns and empirical validation. Issue 77 (August 2018) - Hamid, Brahim; Weber, Donatus
Abstract: Several development approaches have been proposed to handle the growing complexity of software system design. The most popular methods use models as the main artifacts to construct and maintain. The desired role of such models is to facilitate, systematize and standardize the construction of software-based systems. In our work, we propose a model-driven engineering (MDE) methodological approach associated with a pattern-based approach to support the development of secure software systems. We address the idea of using patterns to describe solutions for security as recurring security problems in specific design contexts and present a well-proven generic scheme for their solutions. The proposed approach is based on metamodeling and model transformation techniques to define patterns at different levels of abstraction and generate different representations according to the target domain concerns, respectively. Moreover, we describe an operational architecture for development tools to support the approach. Finally, an empirical evaluation of the proposed approach is presented through a practical application to a use case in the metrology domain with strong security requirements, which is followed by a description of a survey performed among domain experts to better understand their perceptions regarding our approach.